AKIBAT HUKUM HILANGNYA HAK MILIK ATAS TANAH YANG DITERLANTARKAN - Aghniya Nisya Andini, (2021)
The granting of land rights to a person or legal entity is accompanied by an obligation that must be carried out that the state believes that this right is used for the welfare of its rights holders. Land that is neglected because it is not used is one thing that must be considered, because development is growing but the land is decreasing so that it needs control. This research method uses normative juridical method by using literature study data collection method. With this, the results of the research show that the legal consequence of neglected land is the termination of legal ties between the right holder and the land object which will then be taken over by the state, the land object cannot be used as a mortgage, it can be taken over by parties who have physical control for 20 year in good faith; Furthermore, based on Government Regulation No.11 of 2010 that there is no visible use of land use rights by PT. Mojokerto Industrial Park so that the land object is designated as abandoned land, based on this it cuts off the relationship between the owner of the right and the land, resulting in loss of ownership rights to the building use right.